2021
DOI: 10.3390/brainsci11111417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on Cognition and Telomere Length in Healthy Older Women

Abstract: Background: Physical exercise is an effective measure for preventing the onset of cognitive decline and has a direct influence on the aging process. The purpose of this study was to assess the effect of a 6-month physical exercise program on cognition and telomere length in adults over 65 years of age. Method: Seventy-four healthy women were separated into two groups: 41 were included in the intervention group (IG) (72.70 ± 4.127 years and 8.18 ± 1.551 years of education) and 33 in the control group (CG) (71.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Similarly, another factor to take into account in this possible relationship is the regular practice of physical exercise by the study populations. In previous studies, we have confirmed that physical exercise has a positive impact on both telomere length and cognition [ 20 , 21 ]. However, as we have previously mentioned, there is much controversy regarding the possible relationship between TL and cognitive function.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, another factor to take into account in this possible relationship is the regular practice of physical exercise by the study populations. In previous studies, we have confirmed that physical exercise has a positive impact on both telomere length and cognition [ 20 , 21 ]. However, as we have previously mentioned, there is much controversy regarding the possible relationship between TL and cognitive function.…”
Section: Introductionsupporting
confidence: 77%
“…The following protocol was followed for the extraction of DNA from saliva [ 27 , 28 ] and the same laboratory steps were followed as in previous studies [ 21 ]. The cells were isolated by centrifugation and resuspended in Fornace buffer (0.25 M sucrose, 50 mM Tris-HCl pH 7.5, 25 mM KCl, and 5 mM MgCl2), followed by additional centrifugation at 1500 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…There was no interaction between long-term resistance training and telomere length, but a negative impact was found between heavy-resistance training and telomere length when telomeres in skeletal muscle were measured 7,14 . In highly active individuals, exercise can cause muscle damage, satellite cell proliferation (precursor cells), and telomere length shortening in skeletal muscle tissue 6,9,39 .…”
Section: Effect Of Exercise On Oxidative Stress and Telomere Lengthmentioning
confidence: 78%
“…Many studies have been conducted to establish the connection between exercise and telomere length, but still have varying results 5,[13][14][15] . Telomeres are reiterative DNA sequences (5'-TTAGGGn-3') that function to protect genomic DNA from enzymatic degradation 2,5,[16][17][18] .…”
Section: Telomere and Telomerase Activitymentioning
confidence: 99%
“…High altitude hypoxia (5,000 m) causes both tissue damage due to oxidative stress and telomere elongation due to HIF-1α-TERT axis activation ( Wang et al, 2018 ). Physical exercise, which is always accompanied by moderate intermittent hypoxia, increases TL in older persons ( Sánchez-González et al, 2021 ; Sellami et al, 2021 ); it can be speculated that when intermittent hypoxia is applied in a training regime, oxidative stress is minimal; an increase in telomerase expression would lead to telomeres elongation, thereby increasing rejuvenation.…”
Section: Discussionmentioning
confidence: 99%